The Disposition and Metabolism of Bempedoic Acid, a Potent Inhibitor of ATP Citrate Lyase, in Healthy Human Subjects - Amore, Benny M.; Cramer, Clay; MacDougall, Diane; Emery, Maurice G. (Drug metabolism and disposition, 2023)
The disposition and metabolism of bempedoic acid, a selective inhibitor of ATP citrate lyase, were examined in healthy male subjects. After a single administration of [14C] bempedoic acid (240 mg, 113 μ Ci) oral solution, mean concentrations of total radioactivity in plasma as a function of time indicated absorption was rapid with peak concentrations achieved at 1 hour after dose administration. Radioactivity was decreased in a multiexponential fashion with an estimated elimination half-life of 26.0 hours. Radiolabeled dose was predominantly recovered in urine (62.1% of dose) and a smaller amount in feces (25.4% of dose). Bempedoic acid was extensively metabolized with 1.6%–3.7% of dose excreted unchanged in urine and feces combined. Overall, the major clearance route of bempedoic acid is metabolism by uridine 5′-diphosphate glucuronosyltransferases. Metabolism in hepatocyte cultures of human and nonclinical species were generally in agreement with clinical metabolite profiles. Pooled plasma samples were characterized by the presence of bempedoic acid (ETC-1002), which accounted for 59.3% of total plasma radioactivity, ESP15228 (M7; a reversible keto metabolite of bempedoic acid), and their respective glucuronide conjugates. The acyl glucuronide of bempedoic acid (M6) represented 23%–36% of radioactivity in plasma and accounted for approximately 37% of dose excreted in urine. In feces, the majority of radioactivity was associated with a co-eluting mixture of a carboxylic acid metabolite of bempedoic acid (M2a), a taurine conjugate of bempedoic acid (M2c), and hydroxymethyl-ESP15228 (M2b), which collectively accounted for 3.1%–22.9% of bempedoic acid dose across subjects. This study characterizes the disposition and metabolism of bempedoic acid, an inhibitor of ATP citrate lyase for hypercholesterolemia. This work provides further understanding of bempedoic acid clinical pharmacokinetics and clearance pathways in adult subjects.